Modeling and Simulation of Low Current Atmospheric and High-Pressure Helium Plasma Discharges - Maharaj, Avinash; D’Angola, Antonio; Colonna, Gianpiero; Iwarere, Samuel A. (Frontiers in Physics, 2021)
A plasma discharge in a Helium gas reactor at different pressures and at low currents (0.25–0.45 A) has been investigated by Computational Fluid Dynamic modeling coupled with the Maxwell’s equations. The results show different discharge dynamics across the pressure range (0.1–8 MPa), with an arc discharge obtained at high pressure and a low current arc discharge observed at atmospheric pressure. A large density gradient at higher pressure causes a strong natural convection effect in the reactor. This density gradient affects drastically the discharge shape and the velocity field at high pressures while at atmospheric pressure, a lower density gradient was observed resulting in a low velocity magnitude. It has been observed that the velocity magnitude is not affected by the electric current. The discharge electric potential has been calculated by considering the electrical characterization of the electrodes and numerical results have been compared with experimental results. The comparison shows a good agreement between the measured and calculated discharge electric potential at lower pressures. These devices can be used as plasma sources for wastewater treatment.